Towards neutral distribution taxes and vanishing tax effects in the European Union - Christoph Maier; Deborah Schanz (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
The European Union (EU) has no explicit common income tax law. Nevertheless, Court of Justice decisions have driven EU member states to adopt more similar corporate tax systems, and thus, to align the tax treatment of corporate profit distributions - dividends and capital gains. This paper empirically analyzes the influence of the tax preferences of individual and corporate shareholders for the two corporate distribution types - dividends or capital gains - from 1990 to 2012. In the first years of the observation period, European tax systems have provided opposing tax advantages, where individual shareholders have preferred capital gains and corporate shareholders have preferred dividends. To account for these differences depending on the firm's shareholder structure, we derive firm-specific tax preferences for profit distributions. Our empirical analysis reveals that - in line with current literature - the firm-specific tax preferences indeed affect dividend payments. Moreover, we show that in contrast to our detailed study, a simplified approach to measure tax effects on distributions overestimates this influence. In subsequent years, as European Court of Justice decisions have indirectly aligned EU corporate tax systems, we find that tax preferences have converged to a great extent with the tendency to equal tax treatment of dividends and capital gains for both - individual and corporate - shareholder groups. In line with this development, we find that the association of tax preferences and distribution policies vanishes in the last years of the observation period. Our study implies that the EU common regulatory framework, even in the absence of explicit law, can affect corporate distribution decisions and foster neutral taxation of dividends and capital gains across EU member states.
Keywords: G30; G35; H24; H25; 330; tax preferences; dividends; capital gains; distributions; neutral taxation; corporate tax systems; European Union; European Court of Justice